A systematic review and meta-analysis of CBT interventions based on the Fennell model of low self-esteem. (September 2018) - Kolubinski, Daniel C.; Frings, Daniel; Nikčević, Ana V.; Lawrence, Jacqueline A.; Spada, Marcantonio M.
Abstract: Low self-esteem is a feature of several mental health disorders that has been directly treated with Cognitive-Behavioral Therapy (CBT). The aim of our study was to determine the efficacy of interventions for improving low self-esteem in adults by utilizing the model outlined in Fennell (1997; 1998; 1999). A literature search identified 8 studies that met the inclusion criteria of CBT-based interventions for low self-esteem using this model, 7 of which were used in a quantitative synthesis. These studies included weekly group and individual sessions and one-day workshop formats. Summary effect sizes of 1.12 and 0.34 at post-treatment were observed, with low levels of heterogeneity, for weekly sessions and one-day workshops, respectively. Comparable results were found for the reduction of depressive symptoms. Results suggest that CBT-based interventions may be efficacious for treating individuals with low self-esteem, according to changes in self-report measures; however, it is unclear whether these interventions are dissimilar to those aimed at reducing depression.